2016
DOI: 10.1002/cyto.a.22875
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free biomarkers of human embryonic stem cell differentiation to hepatocytes

Abstract: Four different label-free, minimally invasive, live single cell analysis techniques were applied in a quantitative comparison, to characterize embryonic stem cells and the hepatocytes into which they were differentiated. Atomic force microscopy measures the cell's mechanical properties, Raman spectroscopy measures its chemical properties, and dielectrophoresis measures the membrane's capacitance. They were able to assign cell type of individual cells with accuracies of 91% (atomic force microscopy), 95.5% (Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Hepatoma cells with different metastasis ability showed disparity in terms of the distribution patterns of Young’s modulus ( Tian et al, 2015 ). Differences in elastic modulus are found between normal liver, hepatoma, liver embryonic stem cells ( Kim et al, 2013 ; Sun et al, 2016 ; Tsikritsis et al, 2016 ). An AFM topology study showed that the increased surface roughness and reduced cytoskeleton height are associated with curcumin-induced G2/M phase arrest in HepG2 cells ( Jiang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatoma cells with different metastasis ability showed disparity in terms of the distribution patterns of Young’s modulus ( Tian et al, 2015 ). Differences in elastic modulus are found between normal liver, hepatoma, liver embryonic stem cells ( Kim et al, 2013 ; Sun et al, 2016 ; Tsikritsis et al, 2016 ). An AFM topology study showed that the increased surface roughness and reduced cytoskeleton height are associated with curcumin-induced G2/M phase arrest in HepG2 cells ( Jiang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also research into using DEP to concentrate relevant biomarkers for chemical assay . Much of the published efforts into electrokinetic separations for diagnostics have been focused in cell sorting, e.g., .…”
Section: Introductionmentioning
confidence: 99%
“…Threedimensional quantitative phase images of cells are reconstructed from several hundred frames, and the volume, dry mass, and density recorded. Still, the labelfree nature of quantitative phase signatures is attractive for non-destructive cell sorting, and may be added to the list of list of label-free techniques useful for such purposes, including 2D light scattering (6), Raman spectroscopy, stimulated Raman scattering, dielectrophoresis, and atomic force microscopy, to name a few (7). Projections compared to dense multi-frame acquisition would seem to favor higher throughput.…”
mentioning
confidence: 99%
“…These two studies highlight the tradeoff between acquisition throughput versus phase and spatial resolution/information density, which is balanced in the study by Roitshtain, Shaked and coauthors (2). Still, the labelfree nature of quantitative phase signatures is attractive for non-destructive cell sorting, and may be added to the list of list of label-free techniques useful for such purposes, including 2D light scattering (6), Raman spectroscopy, stimulated Raman scattering, dielectrophoresis, and atomic force microscopy, to name a few (7). While these techniques are sensitive to different properties of cells-phase signatures, Mie scattering, biochemistry, lipid droplets, capacitance, and elasticity, in order, for the techniques listed above-they each allow cells to retain viability for future therapeutic or functional testing.…”
mentioning
confidence: 99%